Enhanced butanol-hydrogen coproduction by Clostridium beijerinckii with biochar as cell's carrier. (December 2019) - Wu, Jiwen; Dong, Lili; Zhou, Chunshuang; Liu, Bingfeng; Xing, Defeng; Feng, Liping; Wu, Xiukun; Wang, Qi; Cao, Guangli
Graphical abstract: Highlights: The prepared biochar in this study possesses rich porous and graphitized structure. Butanol and hydrogen yield were simultaneously improved with biochar addition. Biochar regulates reducing power and accelerates acids re-assimilation. Biochar acted as a carrier for cells in fermentation system. The strategy provides an efficient way to enhance ABE fermentation. Abstract: In this study, the effects of biochar on the fermentation performance of butanol-hydrogen coproduction by Clostridium beijerinckii F-6 were investigated. Results showed that the biochar with rich porous and graphitized structure can significantly promote the coproduction of butanol and hydrogen. The productivity of butanol and hydrogen reached 0.148 g/L/h and 0.299 mmol/L/h with biochar addition which were 20.23% and 48.76% higher than that in control without biochar addition, respectively. Moreover, the whole energy conversion efficiency calculated based on the heat value showed increment from 43.69% to 51.75% with biochar addition. Combined analysis of organic acids accumulation and oxidation–reduction potential fluctuation proved that biochar can regulate reducing power during fermentation and accelerate the conversion of acid phase to solvent phase. Scanning electron microscope images showed that biochar acted as carriers for cells absorption. Confirmation experiment further proved that biochar enhanced the butanol tolerant ability of Clostridium beijerinckii F-6.